Clarification of anatomical structure and functions in human nasal cavity by airflow patterns - Erny Afiza, Alias (2016)
As illustrated in Figs. 1.1(a) and (b), the human nasal cavity is defined as air-filled space starting from the nasal vestibule to the opening of pharynx. Being a part of the respiratory system in the human body, it serves as the main conduit for the inspired air between external environment and human lungs. The nasal passages have aerodynamic structures lined with mucosal tissue which act as an air-conditioner to warm and humidify the inhaled air. Besides olfactory function to aid us in sense of smell and taste, the existence of short hairs at the nasal vestibule also help preventing the harmful material from entering our lungs. During inspiration, the inhaled air enters the nostril, goes through the nasal valve, the narrowest area in the nasal cavity [1-1], then passes along the turbinate region before it reaches the lungs where eventually the gas exchange takes place. The nasal valve is located at the anterior region and known to have the greatest nasal airflow resistance due to the smallest cross sectional area within the nasal cavity [1-2]. These can cause either disturbance or assistance to the airflow during nasal respiration.